Prioritization of Diagnostic and Prognostic Biomarkers for Lupus Nephritis Based on Integrated Bioinformatics Analyses - Chen, Zhimin; Lan, Ruilong; Ye, Keng; Chen, Hong; Chen, Caiming; Xu, Yanfang (Frontiers in Bioengineering and Biotechnology, 2021)
Lupus nephritis (LN) is an important driver of end-stage renal disease (ESRD). However, few biomarkers are available for evaluating the diagnosis and prognosis of LN. For this study, we downloaded microarray data of multiple LN expression profiles from the GEO database. We used the WGCNA and R limma packages to identify LN hub genes and differentially-expressed genes (DEGs). We identified nine co-DEGs in the intersection with LN-related genes from the Genecards database. We found DEGs that are primarily associated with immune-related functions and pathways (including with the complement pathway, primary immunodeficiency markers, and MHC-like protein complexes) through our comprehensive GSEA, GO, and KEGG enrichment analyses. We used other LN and SLE validation datasets and discovered six explicitly expressed co-DEGs: HLA-DMA, HLA-DPA1, HLA-DPB1, HLA-DRA, IL10RA, and IRF8 in the LN set; ROC and Precision-Recall curve analyses revealed that these six genes have a good diagnostic efficacy. The correlation analysis with prognostic data from the Nephroseq database indicates that the differential expression of these co-DEGs is associated with a low glomerular filtration rate in that cohort. Additionally, we used a single-cell LN database of immune cells (for the first time) and discovered these co-DEGs to be predominantly distributed in different types of macrophages and B cells. In conclusion, by integrating multiple approaches for DEGs discovery, we identified six valuable biomarkers that are strongly correlated with the diagnosis and prognosis of LN. These markers can help clarify the pathogenesis and improve the clinical management of LN.